Does the German sports system recruit coaches with a functional personality? - Attempting an answer by comparing German basketball coaches with teachers and managers - Wunder, J.; Priem, M.; Wagner, G. G.; Stoll, O. (German Journal of Exercise and Sport Research, 2024)
Currently, there is no theory that identifies the ideal personality type for sports coaches. The study`s goal is to gain insight into the personalities of German basketball coaches and use existing study results from other professional groups to make recommendations for the content of coaches` education. Given the German Olympic Sports Federation`s emphasis on comprehensive coach education that includes personal development, this paper examines the relationship between a coach`s vocation and personality, filling in knowledge gaps about how coaches` personalities appear. The analyses are based on a unique dataset of 360 German basketball coaches and data from the German Socio-Economic Panel Study (SOEP), allowing for a more in-depth comparison of coaches` Big Five personality traits. Using SOEP data from the German general population, teachers, and managers as benchmarks, this paper investigates the relationship between different coaching license levels and distinct personality profiles, providing insights into the characteristics displayed by coaches at various professional levels. The analysed data indicate that lower coaching licence levels are associated with lower neuroticism and more agreeableness, whereas openness, conscientiousness, and extraversion are higher. When comparing coaches to the general population and other occupational groups, A-license coaches have more characteristics that are similar with managers, whilst C-license coaches have more parallels with teachers. Furthermore, examining particular traits and individual comparisons, it is transparent that C-license coaches are more agreeable than A-license coaches. The findings suggest that coach development programs should be improved by incorporating insights from teachers and managers to select coaches and update educational paradigms more carefully. The study emphasizes the importance of traits such as conscientiousness and agreeableness in coaching success and identifies potential areas for intervention to maximize coaching efficacy. In conclusion, this study adds to our empirical understanding of the complex relationships between personality traits, professional roles, and effective coaching on multiple levels. Furthermore, it emphasizes the dynamic relationship between an individual coach`s intrinsic disposition and professional efficacy, showing the importance of tailored interventions to improve coaching outcomes.